Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Let f(x) = 2x + 1 and g(x) = 3x - 3. Find the solution to the equation f(x) = g(x) by sketching the functions.​

Sagot :

Answer:

(4, 9)

Step-by-step explanation:

Given the functions

f(x) = 2x + 1 and g(x) = 3x - 3

Since the solution exists at when f(x) = g(x), then;

2x+1 = 3x -3

Collect like terms

2x - 3x = -3 -1

-x = -4

x = 4

Substitute x = 4 into f(x) = 2x + 1

f(4) = 2(4) + 1

f(4) = 8+1

f(4) =9

Hence the required solution from the graph will be (4, 9)